CLINICAL AND DIAGNOSTIC VALUE OF STUDIES OF ENDOTHELIAL DYSFUNCTION MARKERS IN PATIENTS WITH ISCHEMIC HEART DISEASE - A. Kh. Akhmineeva; O. S. Polunina; L. P. Voronina; I. V. Sevostyanova (Кубанский научный медицинский вестник, 2014)
In this paper we have carried out the diagnosis of the damage of the vascular endothelium in patients with ischemic heart disease (IHD) based on the study of gene of endothelial nitric oxide synthase polymorphism, the condition of vasoregulating function of endothelium, endothelin-1 and the level of type C of natriuretic peptide. 30 patients with IHD and 27 somatically healthy individuals of the Astrakhan region as a control group have been examined. Patients with IHD demonstrated the development of endothelial dysfunction and the prevalence of 4a/4b genotype of endothelial nitric oxide synthase. We have revealed the influence of VNTR-polymorphism on the production of type C of natriuretic peptide and endothelin-1 in ischemic heart disease.